Nickel and copper concentrations in near-bottom water during METEOR cruises M136 and M137 - Florian Scholz (PANGAEA, 2024)
Trace metal and nutrient concentration gradients in near-bottom waters were determined on research vessel meteor cruises M136 and M137 in April and May 2017. Water samples were collected at 0.5, 1.0, 2.0, 3.0 and 4.00.167emm above the seafloor using perestaltic pumps attached to a benthic lander. Trace metal concentrations were determined by ICP-MS. The data are used to evaluate the fate of sediment-derived trace metals in the lower water column across the Peruvian oxygen minimum zone.